PERMASALAHAN PENGAKUAN TERHADAP KELOMPOK-KELOMPOK BELLIGERENT DARI SEGI HUKUM HUMANITER INTERNASIONAL - Marcel Gabriel Pailalah; Sulaiman Hamid; Chairul Bariah (Journal of USU International Law, 2017)
ABSTRACTWars and conflicts have always been a human habit throughout civilization, from the very beginning of human creation on Earth, warfare has always been a determinant of human survival and especially the standing or destruction of civilizations existing in the world. Of the many conflicts that exist, the conflict is a revolt that attracts attention, because of the conflict between the ruling government against armed parties who are not satisfied with the relevant government policy. From here comes the term